KONSTRUKSI PENDIDIKAN KELUARGA SEBAGAI PIONIR DERADIKALISASI PAHAM AGAMA - Dedi Wahyudi; Novita Kurniasih (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
The spread of radicalism is increasingly widespread among the public. Cases of radicalism religious languid actually occurs. The purpose of this research was to formulate education family to be a deradicalization effort for religion understanding. The family as the Foundation of a country can be seen leading guard in an attempt to deradicalization religion understanding. This paper used a variety of sources the library in writing. Based on this research is qualitative research library. As for the results of this research is to use proper parenting and internalization of positive values as well as the quantity of understanding religion in accordance with the principles of Islam rahmatan lil ' alamin family education can make an effort to deradicalization religion understand.